2021
DOI: 10.21608/scumj.2021.172061
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vestibular Function in Patients with Fibromyalgia

Abstract: Background: Fibromyalgia (FM) is a non-inflammatory musculoskeletal chronic syndrome, whose etiology is unknown, characterized by diffuse pain, many patients with FM were reported to have dizziness which is attributed to hypotension and the autonomic nervous system (ANS) dysfunction. Aim: To improve management of patients with fibromyalgia having dizziness. Objective: to assess peripheral vestibular functions in patients with fibromyalgia. Subjects and Methods: After obtaining approval from the Ethics Committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 14 publications
4
7
1
Order By: Relevance
“…This was in agreement with Mohamed et al [19] and Koca et al [20] who stated that the vertigo prevalence was found high with 60% and 84 % frequency respectively in patients with fibromyalgia. According to Mohamed et al [19] the overall dizziness handicap inventory scores were significantly higher in the FM group.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This was in agreement with Mohamed et al [19] and Koca et al [20] who stated that the vertigo prevalence was found high with 60% and 84 % frequency respectively in patients with fibromyalgia. According to Mohamed et al [19] the overall dizziness handicap inventory scores were significantly higher in the FM group.…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with Mohamed et al [19] and Koca et al [20] who stated that the vertigo prevalence was found high with 60% and 84 % frequency respectively in patients with fibromyalgia. According to Mohamed et al [19] the overall dizziness handicap inventory scores were significantly higher in the FM group. They found 78% of FM patients complained of disequilibrium for a long time with complaints of vertigo (mean of 30 months) that could be associated to musculoskeletal problems.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations